Observations of filamentary structures near the vortex edge in the Arctic winter lower stratosphere - C. Kalicinsky; J.-U. Grooß; G. Günther; J. Ungermann; J. Blank; S. Höfer; L. Hoffmann; P. Knieling; F. Olschewski; R. Spang; F. Stroh; M. Riese (Atmospheric Chemistry and Physics, 2013)
The CRISTA-NF (Cryogenic Infrared Spectrometers and Telescope for the Atmosphere – New Frontiers) instrument is an airborne infrared limb sounder operated aboard the Russian research aircraft M55-Geophysica. The instrument successfully participated in a large Arctic aircraft campaign within the RECONCILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) project in Kiruna (Sweden) from January to March 2010. This paper concentrates on the measurements taken during one flight of the campaign, which took place on 2 March in the vicinity of the polar vortex. We present two-dimensional cross-sections of derived volume mixing ratios for the trace gases CFC-11, O 3 , and ClONO 2 with an unprecedented vertical resolution of about 500 to 600 m for a large part of the observed altitude range (≈ 6–19 km) and a dense horizontal sampling along flight direction of ≈ 15 km. The trace gas distributions show several structures, for example a part of the polar vortex and a vortex filament, which can be identified by means of O 3 –CFC-11 tracer–tracer correlations. The observations made during this flight are interpreted using the chemistry and transport model CLaMS (Chemical Lagrangian Model of the Stratosphere). Comparisons of the observations with the model results are used to assess the performance of the model with respect to advection, mixing, and the chemistry in the polar vortex. These comparisons confirm the capability of CLaMS to reproduce even very small-scale structures in the atmosphere, which partly have a vertical extent of only 1 km. Based on the good agreement between simulation and observation, we use artificial (passive) tracers, which represent different air mass origins (e.g. vortex, tropics), to further analyse the CRISTA-NF observations in terms of the composition of air mass origins. These passive tracers clearly illustrate the observation of filamentary structures that include tropical air masses. A characteristic ...